QOL-19. RETURNING TO WORK AFTER A BRAIN TUMOUR – "I THOUGHT I WOULD BE BACK AT WORK THE NEXT WEEK, HOW WRONG I WAS!". (14th November 2022) - Nicklin, Emma; Phang, Isaac; Short, Susan; Hoogendoorn, Petra; Boele, Florien
Abstract: BACKGROUND: Returning to work is important for patients' and their families' well-being, financial circumstances and quality of life. Side-effects of brain tumour (BT) treatment or clinical deterioration from BT progression often causes temporary or permanent inability to work. Aim: To explore the occupational expectations, experiences and satisfaction of BT patients (and their caregivers) following diagnosis/treatment. METHODS: Qualitative semi-structured interviews were conducted with adults diagnosed with a primary BT, in employment/self-employed before diagnosis, currently in follow-up care; and their caregivers. Purposive sampling ensured a mixed BT sample. Participants were recruited from two UK tertiary referral hospitals. Data collection and thematic analysis are ongoing and will be completed by August 2022. RESULTS: To date, 17 interviews (13 patient/4 caregiver) have taken place (59% female, aged 26-73, M= 43). Early findings: 1) Managing expectations : Patients underestimated the impact of surgery and how long it would take to return to work (if they had). Many would have liked more information prior to treatment about potential side-effects (e.g., extreme fatigue). 2) Prior financial support : Most patients suffered financially, often resulting in returning to work before they felt ready. Patients wanted more information prior to treatment about financial support. 3) Ongoing communication : Employers who were emotionally and practically supportive throughout the BT trajectory were highly valued. Some interviewees believed their employers needed to receive better education about BTs. 4) Flexible working : Patients returning to work with enhanced employer support (e.g., reduced hours, working from home and lighter duties) were more satisfied. 5) Better caregiver support : Many caregivers were unsupported by their employers to take carer leave, some worked more to support the family financially. CONCLUSIONS: Preliminary findings offer novel data in an under-researched area. More knowledge around the experiences, barriers and facilitators influencing patients' return to work will allow the planning of tailored occupational support and resources.